Phenolic Compounds Analysis of Root, Stalk, and Leaves of Nettle - Semih Otles; Buket Yalcin (The Scientific World Journal)
Types of nettles (Urtica dioica) were collected from different regions to analyze phenolic compounds in this research. Nettles are specially grown in the coastal part. According to this kind of properties, nettle samples were collected from coastal part of (Mediterranean, Aegean, Black sea, and Marmara) Turkey. Phenolic profile, total phenol compounds, and antioxidant activities of nettle samples were analyzed. Nettles were separated to the part of root, stalk, and leaves. Then, these parts of nettle were analyzed to understand the difference of phenolic compounds and amount of them. Nettle (root, stalk and leaves) samples were analyzed by using High-Performance Liquid Chromatography with Diode-Array Detection (HPLC-DAD) to qualitative and quantitative determination of the phenolic compounds. Total phenolic components were measured by using Folin-Ciocalteu method. The antioxidant activity was measured by using DPPH (2,2-diphenyl-1-picrylhydrazyl) which is generally used for herbal samples and based on single electron transfer (SET).